Improving Student Learning Motivation Through Islamic Educational YouTube Media in Islamic Religious Education Learning (Case Study at SMAN 4 Tuban) - Nadia Salsabella Nur Fitria; Sholikah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Learning motivation is one of the essential factors influencing the success of the Islamic Religious Education (PAI) learning process. Low student motivation is often caused by the use of less varied learning media that have not adapted to technological developments. This study aims to examine the improvement of students’ learning motivation through the use of Islamic educational YouTube media in PAI learning. This research employed a qualitative approach using a case study method conducted at SMAN 4 Tuban. Data were collected through observation, interviews, and documentation. The results indicate that the use of Islamic educational YouTube media can enhance students’ learning motivation, as reflected in increased attention, interest, active participation, and enthusiasm during PAI learning activities. Furthermore, Islamic educational YouTube media helps students understand the learning material in a more concrete and contextual manner. Therefore, the utilization of Islamic educational YouTube media can be considered an effective alternative learning medium to improve students’ learning motivation in PAI learning.